Evaluation of Resistant Genotype Against Brinjal Shoot and Fruit Borer (Leucinodesorbonalis Guenee) - Mannan, MA; Ferdousi, S; Kamal, MM; Das, S (Bangladesh Agronomy Journal, 2022)
Brinjal shoot and fruit borer (BSFB), Leucinodesorbonalis Guenee, is a devastating pest of brinjal (Solanummelongena L.) in all brinjal growing countries across the globe. Ten genotypes of brinjal were evaluated against the pest in experimental field of Khulna University, Bangladesh following arandomized block design with three replications. The genotypes were BARI Hybrid Begun-2, BARI Hybrid Begun-4, BARI BT-4, Begun-4, BARI Begun-9 and BARI Begun-10, Local Cultivar-1, Local Cultivar-2, Local Cultivar- 3, Local Cultivar-4 and BARI Begun-4among the ten brinjal genotypes, reduced shoot and fruit infestation were recorded in local cultivar-1 and BARI Begun 2. On degree of infestation, BARI hybrid BT begun 4 appeared to be resistant while rest of the genotypes were susceptible or highly susceptible. Volume index was documented to be high in BARI hybrid Begun 4 and low in local cultivar 3, while shape index was high in cultivar 2 and low in BARI hybrid begun 4 and BARI Begun-10. BARI Hybrid Begun 4 possessed greater meso and pericarp thickness although those were not resistant. Above all, using resistant genotypes of BARI hybrid BT begun 4 may be considered as a last resort inan optimized IPM package to ensure maximum brinjal productivity. Bangladesh Agron. J. 2021, 24(2): 21-30